Buying Control? 'Locus of Control' and the Uptake of Supplementary Health Insurance - Eric Bonsang; Joan Costa-i-Font; Sonja De New (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper analyses the relationship between locus of control (LOC) and the demand for supplementary health insurance. Drawing on longitudinal data from Germany, we find robust evidence that individuals having an internal LOC are more likely to take up supplementary private health insurance (SUPP). The increase in the probability to have a SUPP due to one standard deviation increase in the measure of internal LOC is equivalent to an increase in household income by 14 percent. Second, we find that the positive association between self-reported health and SUPP becomes small and insignificant when we control for LOC, suggesting that LOC might be an unobserved individual trait that can explain advantageous selection into SUPP. Third, we find comparable results using data from Australia, which enhances the external validity of our results.
Keywords: I12; I13; I18; D15; 330; private health insurance; health care use; risk aversion; locus of control; positive selection; supplementary insurance; Germany; Australia